Prevalence and sociodemographic predictors of anxiety among female nursing officers in a tertiary care hospital: a cross-sectional study - Mehta, Jhanvi; Chaudhry, Kavita; Dutta, Shelly; Vij, Niti (International Journal of Research in Medical Sciences, 2026)
Background: Nursing professionals operating within high-acuity clinical environments face persistent workplace stressors, making them exceptionally vulnerable to psychological morbidity. Female nursing officers may be at extreme risk owing to biological, psychological and sociocultural factors. To estimate the prevalence of anxiety and identify its predictors among working female nursing officers in a tertiary care hospital. Methods: Utilizing a cross-sectional observational framework, we evaluated 264 female nursing officers (ages 21–40) at a tertiary care facility in New Delhi. Psychic and somatic anxiety profiles were quantified via the hamilton anxiety rating scale (HAM-A). Baseline demographic variables were evaluated using Chi-square and Mann-Whitney U tests, while independent predictors of categorical severity were isolated through multivariate logistic regression modelling. Results: The mean age was 29.34±5.87 years. Severe anxiety was observed in 75% of participants. Younger age (≤30 years) was significantly associated with higher anxiety severity (p=0.046). Logistic regression showed that age was an independent predictor, with each additional year reducing the odds of severe anxiety by ~10% (OR=0.90, p=0.013). Marital status and number of children were not significant predictors. Conclusions: There is a high burden of severe anxiety among female nursing officers, particularly among younger individuals. Institutional interventions focusing on early-career nurses are essential.